Identification of self-care practices in patients with hypertension during the COVID-19 pandemic - Widaryati Widaryati; Dwi Prihatiningsih; Ade Putranto Prasetyo Wijiharto Tunggali; Kamilia Naulufar (International Journal of Health Science and Technology, 2023)
The COVID-19 pandemic has exacerbated chronic disease conditions and health disparities, especially in patients with hypertension. Hypertension is the most comorbid disease that increases the risk of worsening and even death in people with Covid-19. Although this disease has a fairly large mortality rate, the practice of independent care carried out by patients can reduce the risk of death by 50% compared to those who do not. This research aims to find out the practice of self-care and related factors in patients with hypertension during the COVID-19 pandemic in the working area of Puskesmas Gamping II Yogyakarta. This research is a cross-sectional study involving 46 respondents with hypertension aged 35 years, and over. The research process was carried out offline by implementing health protocols. Data were collected using the Hypertension Self-Care Activity Level Effects Scale (H-SCALE) questionnaire. The results of this study showed that all participants did not drink alcohol (100%). More than half of the participants had good adherence to physical activity (76.1%), nonsmoking (73.9%), and weight management (58.7%). The lowest self-care practices were dietary adherence (32.6%) and medication (34.8%). Based on data analysis with the Chi-Square test, two factors influence the self-care practice of patients with hypertension: education level associated with adherence to avoiding smoking (p = 0.05) and employment status associated with compliance with weight management (p = 0.01). The results of this study still show that most people with hypertension still experience obstacles in carrying out independent care, especially in diet and taking medication. The restriction of services by healthcare centers during the pandemic and the fear and worry of hypertensive patients affect the compliance of hypertensive patients in conducting health checks at healthcare centers.